Design Development Study Of Mini Trash Skimmer Boat A22 With Packing Technology In East Flood Canal - Wetik, Amelia Berliana Antonia; Pusaka, Augustinus Kindangen (International Journal of Marine Engineering Innovation and Research, 2025)
Garbage is a significant source of water pollution, particularly in the East Flood Canal (BKT) river. This study develops the design of the Mini Trash Skimmer Boat A22 as a practical solution for waste collection in polluted waters. The vessel adopts a catamaran hull to ensure stability and efficiency in skimming operations. With principal dimensions of 3.5 m in length, 2 m in breadth, and 0.8 m in depth, it accommodates a waste bin of approximately 0.4 m³. A conveyor system integrated with hydraulic press technology is applied to compact garbage, thereby increasing storage capacity. Resistance analysis using the Holtrop method in Maxsurf shows that at a speed of 21.26 knots, the vessel experiences a maximum resistance of 8.1 kN, corresponding to an engine power requirement of 8.83 kW. The boat is further equipped with an autonomous navigation module to support operational efficiency and powered by Lifepo4 lithium batteries with one-hour endurance. The results highlight that incorporating packing technology enhances waste-handling capacity, while the combination of catamaran stability and automation makes the Mini Trash Skimmer Boat A22 a promising approach for reducing water pollution in urban waterways.